2022
DOI: 10.3390/jcm11185304
|View full text |Cite
|
Sign up to set email alerts
|

How Does Orthodontic Mini-Implant Thread Minidesign Influence the Stability?—Systematic Review with Meta-Analysis

Abstract: Background: Clinical guidelines are lacking for the use of orthodontic mini-implants (OMIs) in terms of scientific evidence referring to the choice of proper mini-design. Thus, the present study aimed to investigate to what extent orthodontic mini-implant thread design influences its stability. Methods: Search was conducted in five search engines on 10 May. Quality assessment was performed using study type specific scales. Whenever possible, meta-analysis was performed. Results: The search strategy identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Systematic reviews and meta-analysis demonstrated that the use of mini screws is strongly recommended in cases of maximum anchorage than other methods or combinations of treatments and it is associated with a shorter duration treatment time [ 17 19 ]. Whereas other reviews and meta-analysis showed that miniscrews have an acceptably low failure rate linked to insertion sites [ 20 ], to minidesign of screws [ 21 ], and to cortical bone thickness [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and meta-analysis demonstrated that the use of mini screws is strongly recommended in cases of maximum anchorage than other methods or combinations of treatments and it is associated with a shorter duration treatment time [ 17 19 ]. Whereas other reviews and meta-analysis showed that miniscrews have an acceptably low failure rate linked to insertion sites [ 20 ], to minidesign of screws [ 21 ], and to cortical bone thickness [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Additionally, it is understood that the geometry of the implant might affect the pattern of stress distribution along the bone interface. [ 11 12 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors analyzed pitch, thread depth, and shape, concluding that only the first of these three factors is decisive. Implants with a denser thread show greater stability, while thread depth and thread shape are irrelevant [ 13 ].…”
Section: Introductionmentioning
confidence: 99%